Staffing High-Needs Schools: Insights from the Nation's Best Teachers - Berry, Barnett (Phi Delta Kappan, 2008)
This article provides a summary of the five major recommendations from the nation's highly accomplished teachers on the problems in staffing high-needs schools. Insights from these teachers reveal that salary incentives alone will not suffice to attract and retain good teachers for high-needs schools. Working conditions matter--most notably, access to good principals and skilled colleagues, smaller class sizes and student loads, high-quality professional development, and classroom resources necessary to help students meet high academic standards. (Contains 9 endnotes.)